2016
DOI: 10.17051/io.2016.16818
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarının Çokkültürlü Eğitim Tutumları ile Epistemolojik İnançları Arasındaki İlişkinin İncelenmesi

Abstract: ÖZ. Bu araştırmanın amacı öğretmen adaylarının, çokkültürlü eğitim tutumları ile epistemolojik inançları arasındaki ilişkisinin incelenmesidir. İlişkisel araştırma deseninde nicel çalışmanın örnekleminde, kolay ulaşılabilir amaçlı örneklem yöntemi tercih edilmiştir. Araştırmanın katılımcılarını, Marmara bölgesinde bir devlet üniversitesi eğitim fakültesinde öğrenim gören 162 öğretmen adayları oluşturmaktadır. Veri toplama aracı olarak "Öğretmenlerin Çokkültürlü Tutum Ölçeği" ve "Epistemolojik İnanç Ölçeği" kul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 14 publications
2
9
1
8
Order By: Relevance
“…The results indicated that preservice music teachers have multicultural experiences, positive attitudes and beliefs. The result is consistent with the findings of the studies (Çoban, Karaman and Doğan, 2010;Demirci and Özdemir, 2014;Koçak and Özdemir, 2015;Türkan, 2016;Ünlü and Örten, 2013) indicating that pre-service teachers have positive attitudes and beliefs about multicultural education. The findings of the study showed that there is no statistically significant difference in multicultural attitudes and beliefs of pre-service music teachers in terms of gender.…”
Section: Results Discussion and Conclusionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results indicated that preservice music teachers have multicultural experiences, positive attitudes and beliefs. The result is consistent with the findings of the studies (Çoban, Karaman and Doğan, 2010;Demirci and Özdemir, 2014;Koçak and Özdemir, 2015;Türkan, 2016;Ünlü and Örten, 2013) indicating that pre-service teachers have positive attitudes and beliefs about multicultural education. The findings of the study showed that there is no statistically significant difference in multicultural attitudes and beliefs of pre-service music teachers in terms of gender.…”
Section: Results Discussion and Conclusionsupporting
confidence: 91%
“…Araştırmanın ortaya koyduğu bu bulgu, cinsiyet faktörü dikkate alındığında öğretmen adaylarının çokkültürlü eğitime yönelik tutumlarının farklılık göstermediğini ortaya koyan diğer bazı araştırmaların (Bulut ve Başbay, 2014;Koçak ve Özdemir, 2015;Yazıcı, Başol ve Toprak, 2009;Yılmaz ve Göçen, 2013) bulgularıyla paralellik göstermektedir. Ancak farklı bölümlerdeki öğretmen adayları ile çokkültürlü eğitim tutumlarını konu alan diğer çalışmalarda (Çoban, Karaman ve Doğan, 2010;Demircioğlu ve Özdemir, 2014;Türkan, 2016) kadın öğretmen adayları lehine anlamlı farklılık bulunmuştur.…”
Section: Tartişma Ve Sonuçunclassified
See 3 more Smart Citations